WeXel oder Die Musik einer Landschaft - Deutsch, Walter (2014)
Traditional music of the Wechsel, styrian-lower austrian border region, 100 kms south of Vienna. Volume 1 "The religious song" sung during the farmer's traditional two-night corpse-watch at the bier in the house of the deceased. 192 songs with text, music and incipits, 3 CDs with historical recordings, dictionary of local dialect. CD 1: http://e-book.fwf.ac.at/o:672 CD 2: http://e-book.fwf.ac.at/o:727 CD 3: http://e-book.fwf.ac.at/o:762